The context for the thematic grouping of rare diseases to facilitate the establishment of European Reference Networks. Issue 1 (December 2016) - Evangelista, Teresinha; Hedley, Victoria; Atalaia, Antonio; Johnson, Matt; Lynn, Stephen; Le Cam, Yann; Bushby, Kate
Abstract Background In the past few years there has been a political imperative driving the creation of European Reference Networks as these are considered a promising way to achieve equity in access to the most up to date medical care across Europe. The right to equity in the access to care was established by the directive of the European Parliament and of the Council on the application of patients' rights in cross-border healthcare. The particular situation for Rare Diseases whereby sharing of expertise can be regarded as especially valuable, as well as the work that is already in place in the networking of Rare Diseases experts means that Rare Diseases are considered excellent models for the development of European Reference Networks. Discussion To be effective, a Rare Disease network should be based on the common effort of different stakeholders and be built on what is present in the community. European Reference Networks are an excellent model to overcome some of the specificities of rare diseases: scarcity of patients, resources and expertise. European Reference Networks with broad scope will allow the rare disease community the possibility of reaching a larger number of patients and more diversified rare diseases. The practical value of grouping rare diseases in broad networks is well demonstrated in different grouping systems present in Europe (EURORDIS grouping of diseases, "Les filières de santé maladies rares", Orphanet classification and the UK Research Model). Summary In this paper the authors, partners of EUCERD Joint Action, address some of the questions that surround the establishment of European Reference Networks. We will focus on how Rare Diseases could be efficiently grouped in order to constitute European Reference Networks and how they might be structured to allow each and every disease to benefit from networking.